Assessment of the Introduction of Microorganisms Capable of Destroying Toxic Compounds during Seed Germination - Anastasia I. Nechaeva; Violetta V. Klyueva; Inna P. Solyanikova (Engineering Proceedings)
This study evaluated the use of microorganisms to enhance seed germination in contaminated soil. Experiments introduced soil bacteria capable of growing on diesel fuel to clean the soil. Five experimental conditions included controls, soil with diesel fuel (DF), and soil with DF and bacterial suspension (BS) in both sterile and non-sterile conditions. Of 45 isolated microbial cultures, 13 used DF as a carbon source. The soil with 5% DF was slightly polluted. Wheat growth rates were 32% and 34% in DF-treated soil, and 86% and 88% in DF- and BS-treated soil, compared to 82% in the control. Thus, BS significantly boosted wheat seed germination.